Current status and technology development in implementing low carbon emission energy on underground coal gasification (UCG) - Takyi, Shadrack Adjei; Zhang, Yindi; Si, Mengting; Zeng, Fanjin; Li, Yingnan; Tontiwachwuthikul, Paitoon (Frontiers in Energy Research, 2023)
Although coal mining has played a substantial role in world’s development as a critical fuel source for at least 25 years, its value is partly offset by the massive environmental issues it presents during combustion. The shift to a net-zero CO2 emission will open unique possibilities for new coal technological models in which progressive studies and policies, development, and modernization will play a significant role. Therefore, a collection of technologies has been proposed, one of which is cost-effective is the Underground Coal Gasification (UCG) coupled with carbon capture storage (CCS) and utilization technology (CCU) UCG-CCS/CCU. This paper reviews the current status and technology development in implementing low carbon emission energy on underground coal gasification. The study, therefore, leads to discussing the modern stage of underground coal gasification and carbon capture storage development, recent pilot operations, and current developments of the growing market. At the same time, it provides a reference for underground coal gasification combined with CCUS technology.